'Are you Afraid of the Cinema?': Du Cinéma and the Changing Question of Cinephilia and the Avant-Garde (1928-1930) (AmeriQuests, 2015)
This essay considers José Corti’s early issues of Du Cinéma as part of an historical avant-garde complex that, in tandem with literary experiments, shaped another historical approach to early cinema criticism and theory by looking beyond cinephilia as a structuring paradigm. Identifying fear, rather than love, as a powerful avant-garde discourse, I suggest that Du Cinéma and especially the avant-garde writer André Delons forwarded a negative dialectical approach to cinematic thought, inquiry, and research. By investigating the enquête or questionnaire as a central research method in this avant-garde tradition, I reorient our understanding of Du Cinema's claim to the cinema's mutability, and its ability to reveal the limits of knowledge.
Keywords: cinema; cinephilia; cinephobia; Surrealism; Le Grand Jeu; André Delons; José Corti